Vrae rondom die tradisionele bena- dering van die Afrikaanse taalbewe-gings - Plessis, L. T. du (Koers, 1983)
In this article the traditional approach to the history of the Afrikaans language movements, the so-called “Eerste Afrikaanse Taalbeweging” and “Tweede Afrikaanse Taalbeweging” is criticized, more specifically the traditional evaluation of the relation between the “Genootskap van Regie Afrikaners” (GRA) and the first language movement. Under discussion is a new concept of what a language movement is, namely that a language movement is determined mainly by a political and I or a religiousforce. In other words, a politically dominant group of people would make use of the sentimental power of their language the mobilize themselves into a political force. Once they have taken over the power of government their language will most likely receive official status. With this “criterion” in mind, the history of the Afrikaans language movements can be analyzed against the background of Jive different language movements, i.e. the “Oosgrenstaalbeweging” (I860), the “Maleierafrikaanse taalbeweging” (1866), the “Byvbelvertalingsbeweing” (1872), the “Afrikanerbondbeweging” (1880) and the only successful one, the “na-oorlogse taalbeweging” (1914). The latter succeeded because of the immense success of Afrikaner nationalist politics, not because of the beauty or so-called "wonder” of the Afrikaans language, as is often believed. TheGRA was no language movement at all, but part of the “Bybelvertalingsbeweging”. The motive behind this language movement was a religious one: to convert the poor Afrikaans speaking population of the Cape Colony to Christianity. An Afrikaans Bible became a bare essential for this mission and thus explains the efforts of Pannevis and later the GRA to translate the Bible into Afrikaans. The whole effort was not to promote Afrikaans as a language at all. Some other facts concerning the erection of the GRA are put into perspective, for instance: the date 14 August 1875, considered as the dale upon which the GRA was formed, has been proved false. A new dale has been decided upon, which is more accurate, namely 25 September of the same year.